2011
DOI: 10.5243/jsswr.2010.13
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Savings From Adolescence to Young Adulthood: A Propensity Score Approach

Abstract: This paper examines the progression of savings between adolescence and young adulthood. Using data from the Panel Study of Income Dynamics, we ask whether the likelihood of having a savings account in young adulthood and the amount of savings can be significantly predicted by two factors: having a savings account during adolescence and having parents who own assets. Descriptive statistics reveal that adolescents with savings accounts are more often White, employed, and live in households in which the head is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 49 publications
3
38
0
3
Order By: Relevance
“…It should be noted that this influence is positive for the HISEI variable, 10 although the mother's years of education have a negative sign. These results are in line with the conclusions other studies have reached on the influence of parents on their children's financial knowledge (see Grinstein-Weiss et al, 2012;Gudmonson & Danes, 2011or Friedline, Elliot, & Nam, 2011. However, while the mother's educational level is usually a key positive factor in the case of reading, mathematics and science skills (see Baker, Goesling, & LeTendre, 2002), its effect on financial literacy shows a negative influence in our study.…”
Section: Analysis Of the Determinants Of Financial Literacysupporting
confidence: 92%
“…It should be noted that this influence is positive for the HISEI variable, 10 although the mother's years of education have a negative sign. These results are in line with the conclusions other studies have reached on the influence of parents on their children's financial knowledge (see Grinstein-Weiss et al, 2012;Gudmonson & Danes, 2011or Friedline, Elliot, & Nam, 2011. However, while the mother's educational level is usually a key positive factor in the case of reading, mathematics and science skills (see Baker, Goesling, & LeTendre, 2002), its effect on financial literacy shows a negative influence in our study.…”
Section: Analysis Of the Determinants Of Financial Literacysupporting
confidence: 92%
“…Studies have found that most adolescents hold bank accounts and that young adults are even more likely to hold accounts (Friedline, Elliott and Nam ; Elliott ; Friedline ; Kim, Kim and Moon ). In Australia, bank account holding among young adults is nearly universal, as welfare system payments managed by the Department of Human Services (DHS) are often deposited directly into bank accounts (DHS ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although adolescents commonly hold bank and savings accounts, the balances in those accounts tend to be modest (Elliott ; Friedline ; Loke, Choi and Libby ). Low account balances frequently persist into young adulthood because of schooling and large non‐discretionary expenses (Friedline, Elliott and Nam ; Elliott ; Lobaugh, Stephens and Simpson ). Adolescents appear to make their savings decisions in the same way as adults, with considerations of trade‐offs between present and future outcomes and with the development of more conservative risk preferences and precautionary motivations (Otto ; Friedline ; Sutter, Zoller and Glätzle‐Rützler ).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies concerning youth financial capability have dealt with money management and financial behaviour, such as factors influencing saving behaviour (Perry and Morris, 2005;Friedline et al, 2011), attitudes towards money (Oleson, 2004;Engelberg, 2007), the connection between financial knowledge and debt (Lachance et al, 2006;Robb and Sharpe, 2009), and factors influencing credit behaviour (Wang and Xiao, 2009;Huston, 2012;Lachance, 2012). The influences of financial education programmes for the young have been studied too (e.g.…”
Section: Introductionmentioning
confidence: 99%